Implementasi Sistem Pemantauan Bahaya Kebakaran Berbasis ESP32 Dan Node-RED - Saputro, Raihan Akbar; Purwantoro; Solehudin, Arip (Jurnal Sosial Teknologi, 2025)
Fire hazards are one of the disasters that can cause significant losses, especially in densely populated areas. Early detection and monitoring are essential steps to prevent the escalation of such incidents. This study aims to design a fire hazard monitoring system based on the ESP32 microcontroller integrated with the Node-RED platform. The system utilizes the DHT22 sensor to measure air temperature, the MQ-2 sensor to detect smoke or hazardous gases, and a flame sensor to detect direct sources of fire. Data from these three sensors are processed by the ESP32 and transmitted wirelessly using the MQTT protocol to Node-RED, where users can monitor the results through a visual dashboard. In addition, the system is equipped with an automatic notification feature via the Telegram application when dangerous conditions are detected. The test results show that all sensors function accurately and are able to detect the targeted environmental parameters. The system also demonstrates a quick response in delivering alerts when sensor values exceed predetermined thresholds. Integration with Telegram enables users to receive information promptly without the need for continuous manual monitoring. With these advantages, the system can be an effective solution for early fire detection and is expected to improve safety and accelerate emergency response in residential or building environments.